Designing Oxide Aerogels With Enhanced Sorptive and Degradative Activity for Acute Chemical Threats - Novak, Travis G.; DeSario, Paul A.; Long, Jeffrey W.; Rolison, Debra R. (Frontiers in Materials, 2021)
Oxide aerogels are pore–solid networks notable for their low density, large pore volume, and high surface area. This three-dimensional arrangement of pore and solid provides critical properties: the high surface area required to maximize the number of active sites and a through-connected porosity that plumbs reactants to the active interior. In decontamination applications where reactivity beyond adsorption is desired to degrade deleterious molecules, oxide aerogels offer multiple avenues to add oxidative power to this unique arrangement of pore and solid. For protection against chemical warfare agents or toxic industrial chemicals, metal-oxide aerogels with their oxide/hydroxide surfaces afford stability under ambient conditions against competing sorbents such as water and oxygen. In this review, strategies to maximize sorptive capacity and degradation rate by modifying surface functionality, compositing with dissimilar oxides, or adding metallic nanoparticles and the subsequent impact on decontamination performance will be summarized and expected directions for future research will be discussed based on the observed trends.